ANALISIS KINERJA PDAM DELTA TIRTA KABUPATEN SIDOARJO DENGAN MENGGUNAKAN PERSPEKTIF KEUANGAN DAN NON KEUANGAN - PRASETYA PRIBADI, AMI (Universitas Katolik Widya Mandala Surabaya, 2012)
Generally, performance is measured utilize a financial perspective, even though there are non-financial perspective. Non-financial perspectives is the customer perspective, internal business perspective, learning and growth perspective that also important in measuring performance. Customer perspective focuses on the process, because customers would appreciate a short turn around time, especially inservice companies. Internal business perspective focuses on internal processes that will have a major impact on customer satisfaction and achieving corporate financial goals. Learning and growth perspective can identified the infrastructure which built by the company to create growth and long-term performance improvement. Financial perspective and non-financial perspective is the perspective that can determine a good performance, which is increase or decrease. All this time, PDAM â€œDelta Tirtaâ€ Sidoarjo regency performance is not only focused on the financial perspective, but also focus on non-financial perspective. With the current research now a days, this company can complement the non-financial perspective.